The Short-Term Efficacy of Bikini Incision and Traditional Incision in Total Hip Replacement for Elderly Patients via the Direct Anterior Approach - Zhang, Qingsong; Liu, Bo; Zhao, Binghao (Frontiers in Surgery, 2022)
Background The study aimed to explore the short-term clinical efficacy of bikini incision and traditional incision in total hip replacement via the direct anterior approach. Methods The study enrolled 94 patients who underwent total hip replacement using the direct anterior approach between March 2018 and April 2020. They were assigned to the study group and the control group with 47 patients in each group using the random number table method. They received traditional incision and bikini incision, respectively. The operative time, intraoperative estimated blood loss, postoperative pain, length of hospital stay, incision healing, postoperative Harris score, and occurrences of complications were compared between the two groups. Results There was no statistically significant difference in operative time, incision length, and intraoperative estimated blood loss between the two groups (P>0.05). The length of hospital stay was shorter in the study group than that of the control group, and the difference was statistically significant (P<0.05). There was no statistically significant difference in pain severity between the two groups (P>0.05). No incision infection occurred in either group. The study group had small scar areas and scar scores than the control group (P<0.05). There was no statistically significant difference in Harris scores between the two groups at 3 and 6 months postoperatively (P>0.05). The rate of lateral femoral cutaneous nerve injury was lower in the study group than that of the control group, and the difference was statistically significant (P<0.05). Conclusion bikini incision in total hip replacement via the direct anterior approach can shorten the length of hospital stay, promote incision healing, lower the incidence of complications, improve the prognosis and promote recovery of patients and it is worthy of being promoted for wide clinical use.